Identifying drivers of historical genetic decline in an endemic Patagonian rodent, the colonial tuco-tuco, Ctenomys sociabilis (Rodentia: Ctenomyidae) - Tammone, Mauro Nicolás (2018)
Understanding the causes of pronounced losses of genetic diversity in natural populations may provide important insights into the evolutionary significance of these events. However, such analyses are typically based on post-reduction levels and patterns of variability in modern populations, which often lead to results that are biased towards more recent demographic events. In this context, population data recovered from the fossil record provide a powerful resource for studying historical processes of genetic decline. Using radiocarbon dating, stratigraphic analyses and DNA sequencing, we compared genetic variation and relative abundances of fossil specimens from the mid-Holocene to today to evaluate potential explanations for the marked historical loss of genetic diversity in the colonial tuco-tuco (Ctenomys sociabilis), a subterranean rodent that is endemic to Patagonia. We conclude that a general pattern of climatic change during the mid-Holocene, particularly changes in precipitation, led to changes in abundance of suitable habitats for this species. Loss of suitable habitat combined with the unusual demographic structure of this species may have facilitated the decline of populations of C. sociabilis by decreasing gene flow and increasing the potential for fixation of haplotypes due to genetic drift. Our analyses of temporal changes in abundance and genetic diversity in ctenomyids have implications for understanding more widespread patterns of Holocene change in the mammalian fauna of Patagonia.